The water chemistry and microbiome of household wells in Medawachchiya, Sri Lanka, an area with high prevalence of chronic kidney disease of unknown origin (CKDu) - Liza K. McDonough (Nature Portfolio, 2020)
Abstract Chronic kidney disease (CKD) of unknown etiology (CKDu) mostly affects agricultural communities in Central America, South Asia, Africa, but likely also in North America and Australia. One such area with increased CKDu prevalence is the Medawachchiya District Secretariat Division of the Anuradhapura District in the North Central Province of Sri Lanka. Recent research has focused on the presence of various microbial pathogens in drinking water as potential causal or contributing factors to CKDu, yet no study to date has performed a more comprehensive microbial and water chemistry assessment of household wells used for domestic water supply in areas of high CKDu prevalence. In this study, we describe the chemical composition and total microbial content in 30 domestic household wells in the Medawachchiya District Secretariat Division. While the chemical composition in the tested wells mostly lies within standard drinking water limits, except for high levels of fluoride (F), magnesium (Mg), sodium (Na), chloride (Cl) and calcium (Ca) in some samples, we find a frequent presence of cyanotoxin-producing Microcystis, confirming earlier studies in Sri Lanka. Since the total microbial content of drinking water also directly influences the composition of the human gut microbiome, it can be considered an important determinant of health. Several bacterial phyla were previously reported in the gut microbiome of patients with CKD. Using these bacteria phyla to define operational taxonomic units, we found that these bacteria also occur in the microbiome of the sampled well water. Based on available environmental data, our study demonstrates associations between the abundances of these bacteria with geographical distribution, well water temperature and likely fertilizer use in the local surface water catchment area of the individual household wells. Our results reinforce the recommendation that household wells with stagnant or infrequently used water should be purged prior to use for drinking water, bathing and irrigation. The latter is suggested because of the reported potential accumulation of bacterial toxins by agricultural crops. The observation that bacteria previously found in chronic kidney disease patients are also present in household wells requires a more detailed systematic study of both the human gut and drinking water microbiomes in CKDu patients, in relation to disease prevalence and progression.